(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Hepatitis A vaccines are based on classic first-generation inactivated virus vaccines and have been developed by different biopharmaceuticals. HAV is found in the stool, blood of people who are infected and foodborne hepatitis. HBV is a short-term disease and is one of the major causative agents of chronic liver illness. For others, it can become a long-term, chronic infection like liver disease or liver cancer. The analysis of genomic variability of HBV isolates is fundamental for molecular and epidemiological studies. HCV has a higher rate of mutation existing inside an individual as quasispecies. In this sense, this study addresses an analysis of viral hepatitis A/B/C, Herpervirus Simplex (HSV) type 1/2 and the human immunodeficiency virus (HIV) as topics related to comprehensive care for people with sexually transmitted infections (STIs). A total of 2.750 samples were collected from 2.713 patients, of which 38,43% were for HCV; 31,20% for HIV research; 30,25% for HAV and 0,10% for HSV. In all, eight biomarkers of the hepatitis B virus (HBV) were investigated, of which the HBsAg marker was non-reactive in 44,01% (2022 y) and 47.66% (2023 y). About 31,41% (2022 y) and 31.99% (2023y) were reactive for anti-HBs. The highest percentage of investigated samples (98.38%) was recorded in March 2022 with a average proportion of 55.25 ± 12.96 (CV = 0.234) for the non reactive IgM biomarker. The authors suggest follow-up with new serological research associated with molecular assays aimed specifically at reactive and inconclusive results.